Farmers' Knowledge, Perceptions and Management of Black Sigatoka in Small Plantain-Based Farms in Southern Benin - Ahohouendo, Fanou Alain; Togbe, Codjo Euloge; Agbovoedo, Finagnon Robert; Ahohuendo, Bonaventure Cohovi (My University, 2020)
Plantain (Musa paradisiaca) is a key crop, relevant to achieve food security and improve the livelihoods of many households in Africa, particularly in West Africa, where it has become a major staple food. But along with its production, farmers are facing a major foliar disease, the Black Sigatoka that limits the productivity. The yield losses incurred by farmers due to this disease can reach 50%. Knowledge regarding this disease is crucial for effective management of the disease. This paper aims at diagnosing the differences in perceptions and knowledge between farmers and scientists with regard to strategies of managing black Sigatoka on plantain. A survey was conducted on 446 randomly selected farmers using a semi-structured questionnaire in five major plantain growing municipalities (Athiémé, Adja-Ouèrè, Tori-Bossito, Ouinhi, Zè) in Benin. This study came up with knowledge and perceptions of farmers on the symptoms, causes, conducive conditions for disease development, and means of dissemination and strategies for managing black Sigatoka. It appeared that most farmers recognized the disease lesions on the leaves, but failed to associate these symptoms with the targeted disease. In addition, farmers had very limited knowledge of the causal agent, disseminating mechanism and effective management methods. The majority of farmers that are aware of the symptoms (92.7%) associated the yield loss on plantain field with the occurrence of this disease. This appreciation varied from a significant yield loss (54.2%) to a moderate yield loss (45.8%). Most farmers (69%) did not adopt any disease control measures. Deleafing was the most common control method used by 30.2% of the farmers. Apart from this technique, very few farmers reported using synthetic pesticides and biopesticides based on neem leaves (Azadirachta indica). Agricultural research institutes and farmers’ advisory systems were poorly involved in building and managing knowledge related to black Sigatoka in southern Benin. This study has the merit to bring out key information that will help design appropriate programme that would make it possible to manage this disease successfully in short and medium terms with smallholder farmers.
Keywords: Mycosphaerella fijiensis; Musa paradisiaca; Disease Management; Awareness